Nosocomial meningitis and ventriculitis: clinic, diagnosis, prevention (literature review) - M. I. Aybazova; N. V. Dryagina; L. M. Tsentsiper; L. A. Shmidt; N. V. Goncharuk; A. N. Kondratyev (Вестник анестезиологии и реаниматологии)
The objective was to summarize data from the literature on methods of diagnosis and prevention of nosocomial meningitis.Nosocomial meningitis (NM) and ventriculitis are severe, often life-threatening complications in neurosurgery. Currently, postoperative meningitis, shunt infections, and drainage-associated ventriculitis are distinguished. For each of the above groups of diseases, there are specific diagnostic approaches, etiotropic agents, and treatments that differ significantly from community-acquired infections of the central nervous system. Pathogens are represented by a wide range of opportunistic and pathogenic microorganisms, which differ significantly from community-acquired ones. The diagnosis of NM is based mainly on clinical assessment and laboratory examination of cerebrospinal fluid. In most recommendations, there are no precise laboratory criteria for the diagnosis of NM, which is explained by the variability of shifts depending on the microorganism that caused the infection and on the individual characteristics of the patient, as well as the variety of clinical situations. NM prevention is based on minimizing risk factors, includes measures against endogenous and exogenous infection, and can be divided into three stages: preoperative, intraoperative and postoperative. The development of criteria for NM and ventriculitis, the identification of risk factors remains an important problem that has not been definitively solved to date.